Analisis Pengaruh Pemilihan Lokasi Apotek Terhadap Keputusan Pembelian Obat Di Indonesia - Triayu Nur Afifah; Safanny Putri; Nabila Erinaputri; Shifa Aulia Maghfiroh; Huwaydi Azzam Yusuf; Khansa Adristi; Acim Heri Iswanto (Lembaga Pengembangan Kinerja Dosen, 2023)
Pharmacy is a health service facility that aims to help improve health for the community (public health), as well as a place for practicing pharmacists in carrying out pharmaceutical work spread across various regions. Choosing a business location is the main thing to consider in build a business, including pharmacy. A strategic business location is related to transportation efficiency, material properties, product characteristics, and ease of reaching consumers. The purpose of this study is to determine the effect of choosing the pharmacy location on medicine purchasing decisions in Indonesia. The method that used in this study is literature review with 6 research journals that collected and processed pre-existing data using search engines such as Google Scholar and journal databases such as Researchgate and published in 2018-2023. The result shows that pharmacy location is not always a factor in a person's decision to buy medicine, there are other factors such as price, quality of pharmacy service, and etc.